Study of some Brazilian Myrtaceae in Jaboticabal sp - Donadio, L. C. (International Society Horticultural Science, 1997)
The family Myrtaceae is one of the most important related to fruit species. In Brazil it encloses more than 100 species of native fruit from North to South of the country (Giacometti, 1992; Donadio, 1992; Mattos, 1992). The genus Eugenia, Campomanesia, Psidium and Myrciaria are the most important, grouping most of the species of some importance. The germplasm bank of the Universidade Estadual Paulista includes some of the major species. Some characteristics are typical for most of the Myrtaceae fruit species. The most relevant are the long juvenile period presented by the trees, taking long time to produce, when propagated by seed; the slow growing tree behavior; difficult to propagated by vegetative means; large variability in trees obtained by seed propagation. The cited characteristics are commented for some species as well as the fruit quality, from data obtained in trees at the same ecological conditions.The species evaluated are: 1) Eugenia stipitata Mc Vaugh; 2) Eugenia tomentosa Cambes; 3) Eugenia brasiliensis Lam.; 4) Eugenia uniflora L.; 5) Eugenia luchsnathiana Berg.; 6) Eugenia uvalha Cambess; 7) Camponesia spp; 8) Plinia edulis (Veil. Sobral); 9) Eugenia involucrata D.C.; 10) Psidium acutangulum Mart.; 11) Myrciaria dubia Mc Vaugh; 12) Engenia guabiju Berg. The main conclusions based on the data analysed are: the fruits of some species present good general characteristics, mainly for fresh consumption, as high Vitamin C, sugars, pulp and other characteristics; 'Araca-boi' presents some good fruit characteristics, but is more adapted for processing, by its high acidity; Some species present low % of edible portion and need to be improved to gain commercial acceptance. mainly the 'cabeludinha' and 'cambuca'.